2016
DOI: 10.1002/ams2.228
|View full text |Cite
|
Sign up to set email alerts
|

A survival prediction logistic regression models for blunt trauma victims in Japan

Abstract: AimThis research aimed to propose a logistic regression model for Japanese blunt trauma victims.MethodsWe tested whether the logistic regression model previously created from data registered in the Japan Trauma Data Bank between 2005 and 2008 is still valid for the data from the same data bank between 2009 and 2013. Additionally, we analyzed whether the model would be highly accurate even when its coefficients were rounded off to two decimal places.ResultsThe model was proved to be highly accurate (94.56%) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 6 publications
1
15
0
Order By: Relevance
“…In the subclass analysis by TRISS Ps-interval groups, the accuracy of the TRISS model for patients with Ps ≤ 0.95 did not have high performance and the observed-to expected mortality ratio in pediatric patients with Ps ≤ 0.25 was 2.15. Previous studies also suggested similar results, which are as follows: TRISS had lower performance in Japanese blunt trauma patients with Ps < 0.9 than those with Ps ≥ 0.9 [9] and TRISS underestimates survival for pediatric trauma patients with TRISS Ps ≤ 91% [10]. Previous studies suggested that the decreasing trend of in-hospital mortality among trauma patients decreased in recent years would lead the TRISS model to be out of calibration [8,11].…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…In the subclass analysis by TRISS Ps-interval groups, the accuracy of the TRISS model for patients with Ps ≤ 0.95 did not have high performance and the observed-to expected mortality ratio in pediatric patients with Ps ≤ 0.25 was 2.15. Previous studies also suggested similar results, which are as follows: TRISS had lower performance in Japanese blunt trauma patients with Ps < 0.9 than those with Ps ≥ 0.9 [9] and TRISS underestimates survival for pediatric trauma patients with TRISS Ps ≤ 91% [10]. Previous studies suggested that the decreasing trend of in-hospital mortality among trauma patients decreased in recent years would lead the TRISS model to be out of calibration [8,11].…”
Section: Discussionmentioning
confidence: 65%
“…Previous studies based on a Japanese cohort, including children registered in the JTDB during 2005-2008 and 2009-2013 proved that the AUC of TRISS was 0.962 and 0.948 [9,17]. These Japanese studies focused on paediatric patients with blunt trauma and demonstrated that the TRISS had a high performance only for Japanese pediatric patients, as in a previous study [9,17]. Although it is di cult to compare the results between previous studies and this study because of the different periods when the studies were conducted, our results suggest that the TRISS model may be appropriate for Japanese pediatric patients with blunt trauma.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The accuracy of the TRISS method, nevertheless, has various challenges in terms of the investigated area, time, and age. First, previous studies suggested that the TRISS has a low accuracy for survival prediction in patients with higher severity of the injury or younger pediatric patients [ 9 , 10 ]. Second, previous studies suggested that there is a trend to improve the observed-to-expected mortality ratio in major trauma patients, and therefore, new coefficients should be calculated according to these improvements in trauma care for the TRISS to maintain the accuracy for survival prediction [ 9 , 11 ].…”
Section: Introductionmentioning
confidence: 99%